Immobilized invertase - Kotwal, S. M.; Shankar, V. (Biotechnology Advances, 2009)
Invertase is a commercially important enzyme used for the hydrolysis of sucrose. The hydrolysis of sucrose yields an equimolar mixture of glucose and fructose, known as invert syrup, is widely used in food and beverage industries. This enzyme is also used for the manufacture of artificial honey, plasticizing agents used in cosmetics, pharmaceutical and paper industries as well as enzyme electrodes for the detection of sucrose. Immobilization of invertase and its biotechnological applications are reviewed. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Applications; Immobilization; Invert syrup; Saccharase